Packaging Technique for Gain Improvement of Multi-resonance CPW-fed Antenna for Satellite Applications - Jalal Naghar; Azzeddin Naghar; Otman Aghzout; Ana Vazquez Alejos; Francisco Falcone (Institute of Advanced Engineering and Science, 2017)
A suitable technique for gain improvement of multi-resonance CPW-fed antenna for satellite application at Ku-, K- and Ka-bands for user terminals is presented in this paper. New concept of stacking numerous layers with different dielectric material has been also presented. The conventional antenna design consists of a CPW-fed patch antenna with modified CPW elements printed on Rogers TMM4 substrate. In order to improve the antenna performance in term of gain and bandwidth, we propose two different configurations. The first one consists of designing a stacked structure by adding on the top of the single antenna an additional layer with parasitic elements. The dielectric added consists in Rogers RO3010 substrate with a high permittivity of 10.2. The proposed antenna is formed by two layers separated by an air gap; this new configuration provides major reduction on antenna beam width and allows gain enhancement. The second one implement the design of 2×1 and 4×1 series feed antenna arrays based on the conventional CPW-fed antenna. These array configurations are used to achieve higher gain in comparison with stacked solution. Finally we combined both techniques yielding the stacked 4×1 series feed antenna array. Fabricated CPW-fed antenna and the achieved results demonstrate the performance of presented techniques for gain improvements.